(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2022)
There are several uses for turmeric (Curcuma longa L.), a medicinal herb and a spice. Often seen in Asian cuisine. It covers an area of 99200 hectares and produces 167500 tons per year. In India, Pakistan, China, the Indo-Chinese region, Peru and Sri Lanka, it is mostly grown. turmeric comes in a variety of forms, including Alleppey, Armoor, Chintamani, Duggirala, Kasturi, Krishana, Lokhandi, Rajapuri, Salem, Tekurpeta red, and Waigaon, to name a few (Indiresh et.al. 1990). Significant amounts of starch and a tiny amount of an alkaloid can be found in the rhizome. As per Ghosh and Govind (1982), " A wide range of characteristics can be found in the morphology, rhizome, and quality characteristics of turmeric variations (Philip 1978, Philip et. al. 1980). There are several uses for the rhizome in the food and cosmetic industries. The volatile oil and curcumin levels of dry turmeric were both determined to be above normal. For example, it contains mentanil yellow as well as curcumin. According to (Murthy & Subrahamanyam,1982) A food poisoning technique was used to test the extract of Vitexnegundo L. plants against Colletotrichumcapsici (Onkaret. Al., 1993) An alkaloids and tannins found in plant extracts are responsible for the plant’s antifungal properties, phenolicphytotoxins, including cumarins (quinones) (Datar 1999). There are a number of fungi that can attack such a complex and commercially significant crop as turmeric, and the current study provides management guidelines for the treatment of turmeric leaf spot caused by Colletotrichumcapsici.